The molecular pathology of thyroid neoplasms - Thapa, JB (Journal of Pathology of Nepal, 2014)
The Bethesda system of reporting thyroid cytology is being currently adopted worldwide. Rapid advances have been made in the understanding of the genetics of thyroid cancers. Common genetic mutations include RAS, BRAF, p53, B Catenin, and PAX8/PPARγ, genes. BRAF mutations tumours are often aggressive. BRAF mutations commonly affect papillary carcinomas in the BRAF MEK ERF intracellular pathway, whereas RAS mutations commonly affect follicular carcinoma in the PL3 kinase pathway. TK inhibitors, RAS, RET, non RET, PL3, HDAC, DNMT etc. inhibitors are also being considered for therapy against these tumours. DOI: http://dx.doi.org/10.3126/jpn.v4i7.10317 Journal of Pathology of Nepal (2014) Vol. 4, 580-583